Effect of Water Velocity on the Timing of Skeletogenesis in the Arctic Charr, Salvelinus alpinus (Salmoniformes: Teleostei): An Empirical Case of Developmental Plasticity - Richard Cloutier; Alain Caron; Thomas Grünbaum; Nathalie R. Le François (International Journal of Zoology)
Phenotypic plasticity has been demonstrated in fishes but rarely addressed with respect to skeletogenesis. The influence of water velocity on the sequence of chondrification and ossification is studied for the median fins of Arctic charr, Salvelinus alpinus, during a period of 90 days post hatching. Time of appearance, relative position within sequences, and direction of development among serially repeated elements are compared between two velocity treatments. Water velocity has induced changes in the timing of events and to a lesser extent on the relative sequence events in the locomotor system. Ossification is more responsive to water velocity than chondrification, and early-forming elements are less responding than late-forming elements. Directions of development are fairly conservative. It is suggested that a faster sustained swimming (behavioural adaptation to a higher water velocity) could induce differential mechanical stresses on developing skeletal elements involved in locomotion and therefore induce changes primarily in the timing of the ossification.